Manufacture of Npk Liquid Fertilizer From Market Waste and its Utilization in Prei Onion Plants (allium ampeloprasum var. Porrum l. J. Gayvar. Porrum l. J. Gay) and Cayenne Pepper (capsicum frustescens l.) in Singgalang - Tanah Datar Regency and Pauh Duo - Abdul Razak; Des M; Wirdaningsih Wirdaningsih; Relsas Yogica; Fitra Arya Dwi Nugraha (Pascasarjana, Universitas Negeri Padang, 2020)
The purpose of this service activity is to train 2 group partners in Nagari Singgalang, Tanah Datar Regency and Pauh Duo nan Batigo, Solok Selatan Regency to be able to process organic waste into compost or organic fertilizer There are also farmer group partners and women cultivators who take part in PKK activities in the village of Pauh Duo Nan Batigo in South Solok Regency to grow vegetables. They number less than 35. Methods of community service are as follows: socialization and coordination of related parties, providing compost houses, procurement tools, and materials, compost making training Results obtained: a group of capable partners has processed market organic waste into organic liquid compost PK in the two villages. Keywords: NPK, waste, liquid fertilizer, prei onion, cayenne pepper